Mapping the Future of Undergraduate Career Education Equitable Career Learning, Development, and Preparation in the New World of Work - Buford, Melanie V.; Sharp, Michael J.; Stebleton, Michael (Taylor & Francis, 2023)
This timely book explores current trends and future possibilities for undergraduate career education, the nature of the changing workplace, and its impact on students in colleges and universities. Built on decades of experience in career development and professional learning, the editors raise and investigate multiple critical issues facing career educators in higher education today: preparing students for the future of work; exploring the increasing centrality of experiential learning in career education; examining innovative paradigm shifts in career education; and developing strategies for equity-focused and inclusive programming for all students. Reckoning with the effects of COVID-19 on the world of career development, this book draws on contributions from leading scholars, entrepreneurs, and practitioners from across the fields of education, business, STEM, and the humanities to offer an inclusive and innovation-focused approach to supporting scholars, practitioners, and students involved with career education, development, and counseling for a new generation-and a new world of work.